Implementation model architecture software defined network using raspberry Pi: a review paper - Oki Marzuqi; Agus Virgono; Ridha Muldina Negara (Universitas Ahmad Dahlan, 2019)
Software defined network (SDN) made with basic concepts that are different from traditional networks in controlling the network, the separation between the control layer and forwarding layer on different devices allows the administrator to adjust the control plan for all devices centralized in one action, while in traditional network, the control and forwarding layers are located in the infrastructure making network administrator must manage devices one by one. Research using single board computers on network technology provides an opportunity to implement SDN architecture. Raspberry Pi has sufficient ability. QoS results meet the ITU-T G.1010 reference which indicates that Raspberry Pi can be used on designed networks.